A R2R3-MYB Transcription Factor Regulates the Flavonol Biosynthetic Pathway in a Traditional Chinese Medicinal Plant, Epimedium sagittatum - Huang, Wenjun; Khaldun, A. B. M.; Chen, Jianjun; Zhang, Chanjuan; Lv, Haiyan; Yuan, Ling; Wang, Ying (Frontiers in Plant Science, 2016)
Flavonols as plant secondary metabolites with vital roles in plant development and defense against UV light, have been demonstrated to be the main bioactive components in the genus Epimedium plants, several species of which are used as materials for Herba Epimedii, an important traditional Chinese medicine. The flavonol biosynthetic pathway genes had been already isolated from E. sagittatum, but a R2R3-MYB transcription factor regulating the flavonol synthesis has not been functionally characterized so far in Epimedium plants. In this study, we isolated and characterized the R2R3-MYB transcription factor EsMYBF1 involved in regulation of the flavonol biosynthetic pathway from E. sagittatum. Sequence analysis indicated that EsMYBF1 belongs to the subgroup 7 of R2R3-MYB family which contains the flavonol-specific MYB regulators identified to date. Transient reporter assay showed that EsMYBF1 strongly activated the promoters of EsF3H (flavanone 3-hydroxylase) and EsFLS (flavonol synthase), but not the promoters of EsDFRs (dihydroflavonol 4-reductase) and EsANS (anthocyanidin synthase) in transiently transformed Nicotiana benthamiana leaves. Both yeast two-hybrid assay and transient reporter assay validated EsMYBF1 to be independent of EsTT8, or AtTT8 bHLH regulators of the flavonoid pathway as cofactors. Ectopic expression of EsMYBF1 in transgenic tobacco resulted in the increased flavonol content and the decreased anthocyanin content in flowers. Correspondingly, the structural genes involved in flavonol synthesis were upregulated in the EsMYBF1 overexpression lines, including NtCHS (chalcone synthase), NtCHI (chalcone isomerase), NtF3H and NtFLS, whereas the late biosynthetic genes of the anthocyanin pathway (NtDFR and NtANS) were remarkably downregulated, compared to the controls. These results suggest that EsMYBF1 is a flavonol-specific R2R3-MYB regulator, and involved in regulation of the biosynthesis of the flavonol-derived bioactive components in E. sagittatum. Thus, identification and functional characterization of EsMYBF1 provide insight into understanding the biosynthesis and regulation of the flavonol-derived bioactive components in Epimedium plants, and also provide an effective tool gene for genetic manipulation to improve the flavonol synthesis.